Mechanochemical transduction of cells on extracellular matrix protein. - Chan, Jia Hui. (2010)
The physical basis of disease has been neglected in the current focus of medicine despite evidences showing that alterations to the tissue structure or mechanics have led to problems of pain and morbidity. Therefore, a study was conducted with the aim of gaining an insight about mechanics involvement in molecular biology. It is understood that cellular activities are mediated by many different factors and one of which is the cell-extracellular matrix (ECM) protein interactions. The scope of the study will thus be covering on this particular aspect by investigating the differences in cell traction forces (CTFs) exerted by adherent smooth muscle cells (SMCs) on polyacrylamide gel (PAG) substrate conjugated with different ECM proteins, namely Collagen I, Fibronectin and Laminin. Cell traction force microscopy methodology was adopted to analyze the traction force field by applying particle image velocimetry (PIV) analysis and linear finite element (FEA) analysis for each cell sample. From a minimum sample size of 30 for each extracellular matrix protein, distribution curves were plotted to provide trends related to the effect of different cell-ECM protein interactions. The findings from these trends were subsequently compared with literature to provide biophysical evidence of how cellular activities can be mediated through cell-ECM protein interactions.